Labor outcome among obese postdate women undergoing labor induction - Hassan, Mahmoud F.; Rund, Nancy M. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Maternal obesity and postdate pregnancy are common findings among pregnant women worldwide. We aimed to evaluate the influence of maternal obesity on the outcome of labor induction for postdate pregnant women. Methods: We conducted a prospective observational study to compare 118 obese women (≥30 kg/m2) with 118 non-obese women (<30 kg/m2) undergoing labor induction for postdate pregnancy (≥41 weeks). We induced all participants by a uniform protocol according to the Bishop score. The primary outcome measures were the cesarean delivery (CD) rate and the rate of failed induction. Secondary outcomes included prolonged induction- delivery time, prolonged first and second stage of labor, and rate of instrumental delivery. We performed a multivariate regression model to assess for the relation between obesity and the study outcomes of interest. Results: Cesarean delivery was significantly higher in obese women when compared with non-obese women (25.4% vs. 12.7%, p=0.02). Likewise, failed induction rate was significantly lower among non-obese women (5.1% vs. 14.4%. p=0.026). Obese women had increased odds for CD (adjusted odds ratio: 2.24; 95% confidence-interval: 1.13-4.33), failed induction rate (adjusted OR 2.96; 95% CI: 1.15-8.17), prolonged induction-delivery time (adjusted OR 4.57; 95% CI: 1.42-14.74), prolonged first stage of labor (adjusted OR 3.32; 95% CI: 1.07-9.89), prolonged second stage of labor (adjusted OR 4.21; 95% CI: 1.27-13.62), and rate of instrumental delivery (adjusted OR 2.97; 95% CI: 1.16-8.23). Conclusions: Obesity adds more risk to postdate women undergoing induction of labor. Obesity increases the incidence of CD and failed induction among induced postdate women. Therefore, obstetricians should encourage obese women to reduce weight before getting pregnant, and to comply with the optimal weight gain during pregnancy in attempt to reduce the rates of postdating, CD and failed induction.